An effective method to summarise the outcomes of questionnaire-based studies in systematic reviews. (17th November 2022) - Tewari, Nitesh; Goel, Shubhi; Haldar, Partha; Mathur, Vijay Prakash; Srivastav, Sukeshana
Abstract: With an increased number of questionnaire-based knowledge, attitude, practice and other types of studies, there is a need to perform evidence-based research in such designs as well. The systematic reviews (SR) and meta-analyses (MA) of the questionnaire-based studies are difficult to conduct and summarise due to the wide variations in the questions included in each of them. The presentation of these reviews often leads to ambiguous conclusions, and meta-analysis is not possible due to wide heterogeneity. This paper aims to highlight a method known as the 'Knowledge-Attitude-Practice' or 'KAP' Heat Map, which was developed and validated for the effective presentation of the outcomes of varied questionnaires in systematic reviews.